Biodiversity and patents: Overview of plants and fungi covered by patents. Issue 5 (29th September 2020) - Simmonds, Monique S. J.; Fang, Rui; Wyatt, Lilybelle; Bell, Elizabeth; Allkin, Bob; Forest, Felix; Wynberg, Rachel; da Silva, Manuela; Zhang, Ben Gang; Shi Liu, Jiu; Dong Qi, Yao; Demissew, Sebsebe
Social Impact Statement: Patents can be used as a measure of innovation and to illustrate the commercial potential of plant and fungal biodiversity. The proportion of plant species named in patents represents only 6.2% of plant species, whereas the proportion of fungi is likely less than 0.4%. Fungi clearly justify further research. Innovation on a species usually drives more innovation on that species. We suggest that we should ensure that commercialization frameworks encourage studies on a greater diversity of plants and fungi. This could not only increase the range of biodiversity‐based products and associated income but also incentivize their conservation and encourage more fundamental research. Summary: In this review, patents are used as a measure of innovation, and data show that a low proportion of plant and fungal biodiversity is mentioned in patents. The proportion of plant species named in patents represents only 6.2% of plant species, whereas the proportion of fungi is most likely less than 0.4%. The number of species within a plant family mentioned in patents varies greatly. The following families having the greatest numbers: Asteraceae with 1, 445 species (4.5% of species), Fabaceae with 1, 299 species (5.8%), Poaceae with 1, 008 species (8.5%), and Rosaceae with 718 species (12.7%). Case studies from Brazil, Ethiopia, and South Africa explore some of the controversies associated with patenting, especially when patents have not taken prior art into account. In contrast, a case study on plants and fungi used in traditional Chinese medicine illustrates their economic value and their potential to support new innovations. Innovative ways to use plant and fungal biodiversity has the potential to generate wealth, reduce poverty, improve human well‐being and in theory incentivize biodiversity conservation. International and national policies and laws that aim to facilitate equitable benefit‐sharing associated with access to and use of genetic diversity need to be reviewed to help facilitate innovation, as well as ensure that the rights of communities to use these resources are recognized and supported. Abstract : Patents can be used as a measure of innovation and to illustrate the commercial potential of plant and fungal biodiversity. The proportion of plant species named in patents represents only 6.2% of plant species, whereas the proportion of fungi is likely less than 0.4%. Fungi clearly justify further research. Innovation on a species usually drives more innovation on that species. We suggest that we should ensure that commercialization frameworks encourage studies on a greater diversity of plants and fungi. This could not only increase the range of biodiversity‐based products and associated income but also incentivize their conservation and encourage more fundamental research.